2008
DOI: 10.1021/ic800985k
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structures, Phase-Transition, and Photoluminescence of Rare Earth Carbodiimides

Abstract: Rare earth carbodiimides with the general formula RE 2(CN 2) 3 crystallize with two modifications. A monoclinic( C2/m) modification is obtained for RE = Y, Ce-Tm and a rhombohedral ( R3 c) modification for RE = Tm-Lu. The space group R3 c is confirmed by single-crystal structure determination on Lu 2(CN 2) 3 and indexed powder patterns of RE = Tm, Yb and Lu. The use of diverse chemical syntheses conditions for Tm 2(CN 2) 3 revealed the dimorphic character of this compound. In addition, pressure experiments on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
44
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 22 publications
0
44
0
1
Order By: Relevance
“…The structure of LiIn(CN 2 ) 2 is related to the structure of rhombohedral RE 2 (CN 2 ) 3 compounds, having planar cation and anion layers [10,30,31]. The distances between the adjacent cations in Y 2 (CN 2 ) 3 structure are between 379 and 396 pm, in LiIn(CN 2 ) 2 the In-In distances are shorter, about 333-343 pm.…”
Section: Luminescencementioning
confidence: 99%
“…The structure of LiIn(CN 2 ) 2 is related to the structure of rhombohedral RE 2 (CN 2 ) 3 compounds, having planar cation and anion layers [10,30,31]. The distances between the adjacent cations in Y 2 (CN 2 ) 3 structure are between 379 and 396 pm, in LiIn(CN 2 ) 2 the In-In distances are shorter, about 333-343 pm.…”
Section: Luminescencementioning
confidence: 99%
“…In the last decade, the chemistry of metallated carbodimiides (MNCN) group has been very developed because of its potential applications in the electronic and magnetic fields [1][2][3][4][5][6][7][8][9][10][11] . In the series of germylcarbodiimides, through the full study of the polycarbodiimidogermylene (Ge II -NCN) n 12 , it has been found that this product shows a conductivity of 10 -2 Scm -1 , and is classified as semiconductor material.…”
Section: Introductionmentioning
confidence: 99%
“…This result has been explained by the presence of a high electronic delocalization in the polymer chain, due to the alternation of metal atoms and -N=C=N-electron rich spacers group [12][13][14][15] . An important interest has also been observed for the metalcarbodiimide chemistry using rare earth, transition and semi-metals for their potential magnetic, electronic and ceramics properties [1][2][3][4][5][6] . For instances, in the case of magnetic properties, X. Liu 5 and coworkers has described the preparation of MnNCN which has presented antiferromagnet behavior with an ordering temperature below 30 K. An example of properties, in the electronic fields, has been reported for CuNCN 2 which has been considered as a semi-conductor with a resistivity of about 1kΩcm at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…[13,15,16] Due to the high thermal stability of binary rare earth oxides, carbides and nitrides specific synthesis routes are inevitable to expand the field of lanthanide (oxo)nitridocarbonates. Metathesis reactions between lanthanide halides and lithium cyanamide studied by Meyer et al [17] gave access to various rare earth carbodiimide compounds characterized in the last years: La 2 O(CN 2 ) 2 ; [18] Ln 2 (CN 2 ) 3 (Ln = Y, La -Lu); [19] Ce 3 (CN 2 ) 3 N; [20] LiEu 2 (CN 2 )I 3 ; [21] EuCN 2 . [22] Compared to the rapidly growing field of carbodiimide chemistry other rare earth (oxo)nitridocarbonates such as cyanates, dicyanamides or carbamates have been rarely mentioned in the literature.…”
Section: Introductionmentioning
confidence: 99%